Analisis Problematik Episode Dying for Pie Pada Film Animasi SpongeBob - Maysa Dwi Artha Hutagalung; Deby Rahmawati (Peneliti.net, 2023)
SpongeBob SquarePants is an animated film that is loved by children aged 6-11 years, even teenagers and adults often watch this film. SpongeBob films are among the most popular animations because they often take references from popular culture. Do you know why the main character in this film is named SpongeBob? As we all know, SpongeBob is a sea sponge who is innocent, passionate and playful. However, there are several things in this episode of the animated film that still cannot be solved or what are often called problematic. The purpose of this study is to determine the characters and narrative functions in the SpongeBob episode Dying for Pie animated film using Vladimir Propp's theory.